Interactive biology learning system (IBLS) / Vija Kumar Ganapathy Pillay - Vija Kumar, Ganapathy Pillay (2002)
Interactive Biology Learning System (IBLS) is a web-based learning-teaching system for upper secondary school level specifically to students who are taking the General Certificate of Secondary Education (GCSE). Secondary school students and teachers are the target of this system. It can be a teaching tool or as a self-learning program. The strenght if IBLS is that it provides lessons to educate users on the meaning of biology specifying on the topics namely Life Processes, Green Plants, Human as an Organism, Varition, Inheritance and Evolution. There are tutorials that test the student’s and worksheets that canbe downloaded for further practice. Games based on the topics will be created for students to increase the interest of learning biology and to test their skills. This project aims to create an effective and interesting learning tool to enable students learn an enjoy biology at the same time, IBLS is a web-based application could increase the number of computer literate students through an interactive and interesting way of learning biology. The waterfall model with prototyping will be development model used to develop IBLS. The main advantage of this system is that the process can be tailored to meet the specific requirements yet possibly changing needs of any application. As IBLS is an interactive multimedia web-based system, tools that will be used for the development comprises of Macromedia Flash 5, Macromedia Dreamweaver 4, and Abode Photoshop, ASP, HTML and JavaScript are the programming languages that will be used and Microsoft Access 2000 serves as the database to store information of the system.